EVELOPMENT OF EMBRYOS AND LARVAE METAMORPHOSIS OF NEMO ANEMONEFISH AMPHIPRION OCELLARIS CUVIER 1830 IN THE LABORATORY - Loc, Ha Le Thi; Thuy, Nguyen Thi Thanh; Huynh, Ho Ngoc (Vietnam Journal of Marine Science and Technology, 2009)
Nemo Anemonefish (Amphiprion ocellaris) embryos had been taken well care by parental fish. The embryos  developed normally in 7 - 8 days in incubated temperatures 27 ± 1 0C; salinity 34 – 35 ppt; pH ranged from 8.1 to 8.3; O2 > 5 mg/l; NH3 + < 0.1 mg/l and NO2- < 0.05 mg/l. The study had been carried out from January 2009 to August 2009.The eggs were sticky and looked like capsules with lengths of 2.59 ± 0.14 mm and widths of 0.93 ± 0.07 mm. Ten hours after spawning the embryos developed into Blastula. Nineteen hours after spawning, the  embryos developed into Gastrula. After 38 hours, the hearts were clearly observed beating at a rate of 78 times per minute, and the iris was visible. On the fifth-day the pectoral, dorsal and ventral fin folds were well defined. On the sixth-day the gills were more apparent, vestiges of the gill rakers were visible, the mouth  could be distinguished, and the anus could be seen. On the seventh-day the yolk was absorbefacient, the embryonic mouth opened, and the larvae could eat immediately after hatching.The larvae were 3.63 ± 0.1 mm in length, fed on Brachionus plicatilis with a density of 5 inds/ml and Nannochloropsis oculata with a density of 106 inds/ml for the first 5 days. After that, the larvae were fed on Nauplii of Artemia with a density of 5 inds/ml and after one month the fish were fed on fresh shrimp meat.The 30 days old fishes were 12.84 ± 0.60 cm in length, 4.28 ± 0.18 cm in height and 0.0376 ± 0.0025 g in weight. The fishes were in bright orange color with two white stripes: one was at the middle of the back and the other was at the gill cover.The 60 days old fishes were 15.96 ± 0.66 cm in length, 5.50 ± 0.61 cm in height and 0.0842 ± 0.0191 g in weight. The fishes developed well with three white stripe-orange body as an adult nemo.